The impact of plant density on the seed yield and the spring field pea’s yield component - Krizmanić, Goran (Array, 2020)
The spring field pea is one of the most important coarse legumes. This study was carried out to investigate the response of a spring field pea variety to three plant densities (50, 100, and 150 plant m-2) during the 2017 and 2019 growing seasons in eastern Croatia. The field study was set up as a Randomized Complete Block Design (RCBD) in four replications. The results have demonstrated a significant effect of the plant densities and the growing seasons on the seed yield and on the following yield components: plant height and the number of pods/plant. The effect of plant densities on the number of seeds/pod and the thousand-seed weight was not significant. As for a growing season, the highest seed yield, plant height, the number of pods/plant were obtained in the second growing season. Furthermore, a maximum seed yield was recorded at the 150-plant m-2 plant density. This study has demonstrated that planting the spring field pea at different plant densities significantly modifies the spring field pea yield, plant height and number of pods/plant.